Lucan's Use of Caesar's Commentarii: Some Remarks on Lucan. V 461-475 and Caes. BCIV. III 18-19 - Plago, Mariusz (Polskie Towarzystwo Filologiczne i Uniwersytet Wrocławski, 2020)
In scholarship on Lucan, more and more emphasis is being placed on the connection of his poem with Caesar’s Commentarii de bello civili. It is argued that the Civil War remains in constant interaction with Caesar’s text. This article aims to analyse one example of such interaction by undertaking a juxtaposition and a close reading of Lucan. V 461–475, the narrative about the two armies encamped on the river Apsus in Epirus, and Caes. BCiv. III 18–19. These two sections are firmly connected by common motifs that do not appear together elsewhere, a similar order of narrative episodes, and the strong commitment of the narrator. The first part of the article focuses on how Lucan debunks Caesar’s propaganda and at the same time creates another one, expressed by his narrator. In the second part, an attempt is made to show that Lucan’s text is more complex and that it includes other voices, which also undermine the epic narrator’s fervent utterances.